Frequency of Obstructed Labor in Teenage Pregnancy - Shaikh, Shahida; Shaikh, AH; Shaikh, SAH; Isran, B (Nepal Journal of Obstetrics and Gynaecology, 2013)
Aims: Teenage pregnancy has globally recognized as high risk pregnancy. Under grown pelvic bones at delivery pose greater risk of obstructed labour in such young girls resulting in poor feto-maternal outcome. Objective of this study was to determine the frequency of obstructed labor in teenage pregnancy and to know fetomaternal outcome. Methods: This Cross Sectional Observational study was conducted at department of Obstetrics and Gynecology unit I and II, Shaikh Zyed Women Hospital Chandka Medical College, Shaheed Mohtarma Benazir Bhutto Medical University Larkana Sindh Pakistan from 1st January 2010 to 31st December 2010. 468 women admitted with obstructed labour of all age groups, out of these which 257 patients were teenage mothers. Patients selected after fulfilling selection criteria. Obstructed labour in teenage patients wasdiagnosed on the basis of history of prolonged labour and clinical presentation. Demographical characteristics noted. Mode of the delivery and fetomaternal outcome was observed. Statistical analysis was performed using SPSS. 12 version. Results: Total deliveries in both units during study period were 9000. Among them 468(5.2%) patients found to have obstructed labour. Out of these 257(2.85% of total) patients were teenagers.. 82% (210) teengers were non booked and admitted in emergency while only 18 %(47) came through OPD having a single visit. Mean age was 16±2 years and parity was 2±1.5.Mode of delivery was LSCS in 84% (214) ,assisted vaginal delivery in 12% (32) and 4% (11)had spontaneous delivery with episiotomy. Cephalopelvic disproportion remained the commonest reason of obstruction (66%). 1.94% (5) of patients died of septicemia .PPH seen in 41% (105),1.1% (3) had scar dehiscence due to prolonged trial by untrained birth attendant.1.94% (5) patients developed vesicovaginal fistula later on. Perinatal mortality was around 54.6% (142) while 44.75 % (115) babies born alive. Conclusions: Adolescent pregnant women not only face pregnancy related problem but also they are prone to have obstructed labour due to their developing pelvic bones. Obstructed labour is one of the most common and preventable causes of maternal and perinatal deaths and disabilities. Nepal Journal of Obstetrics and Gynaecology / Vol 7 / No. 1 / Issue 13 / Jan- June, 2012 / 37-40 DOI: http://dx.doi.org/10.3126/njog.v7i1.8834